Shifting up a gear with iDNA: From mammal detection events to standardised surveys. Issue 7 (23rd May 2019) - Abrams, Jesse F.; Hörig, Lisa A.; Brozovic, Robert; Axtner, Jan; Crampton‐Platt, Alex; Mohamed, Azlan; Wong, Seth T.; Sollmann, Rahel; Yu, Douglas W.; Wilting, Andreas
Abstract: Invertebrate‐derived DNA (iDNA), in combination with high throughput sequencing, has been proposed as a cost‐efficient and powerful tool to survey vertebrate species. Previous studies, however, have only provided evidence that vertebrates can be detected using iDNA, but have not taken the next step of placing these detection events within a statistical framework that allows for robust biodiversity assessments. Here, we compare concurrent iDNA and camera‐trap surveys. Leeches were repeatedly collected in close vicinity to 64 camera‐trap stations in Sabah, Malaysian Borneo. We analyse iDNA‐derived mammalian detection events in a modern occupancy model that accounts for imperfect detection and compare the results with those from occupancy models parameterised with camera‐trap‐derived detection events. We also combine leech‐iDNA and camera‐trap data in a single occupancy model. We found consistent estimates of occupancy probabilities produced by our camera‐trap and leech datasets. This indicates that the metabarcoding of leech‐iDNA method provides reasonable estimates of occupancy and may be a suitable method for studying and monitoring mammal species in tropical rainforests. However, we also show that a more extensive collection of leeches would be needed to assess mammal biodiversity with a robustness similar to that of camera traps. As certain taxa were only detected in leeches, we see great potential in complementing camera‐trap studies with the iDNA approach, as long as the collection of leeches follows a robust and standardised sampling scheme. Synthesis and applications . Here, we describe an approach to analyse detection records of mammals derived from leech samples using an occupancy framework that accounts for leech‐specific factors influencing the detection probability. We further combined camera trap and leech data, which lead to increased confidence in occupancy estimates. Our approach is not restricted to the processing of leech samples, but can be used for the analysis of other invertebrate DNA and environmental DNA data. Our study is the first step to shift the application of invertebrate DNA studies from opportunistic ad‐hoc collections to the systematic surveys required for long‐term management of wildlife populations. Abstract : Here, we describe an approach to analyse detection records of mammals derived from leech samples using an occupancy framework that accounts for leech‐specific factors influencing the detection probability. We further combined camera trap and leech data, which lead to increased confidence in occupancy estimates. Our approach is not restricted to the processing of leech samples, but can be used for the analysis of other invertebrate DNA and environmental DNA data. Our study is the first step to shift the application of invertebrate DNA studies from opportunistic ad‐hoc collections to the systematic surveys required for long‐term management of wildlife populations. Abstrak: DNA yang diperolehi dari invertebrat (iDNA), dengan high throughput sequencing, telah dicadangkan sebagai sesuatu kaedah survei spesies vertebrata. Sebelum ini, kajian hanya menunjukkan bahawa spesies vertebrata boleh dikesan dengan kaedah ini, tetapi belum digunakkan dalam rangka kerja statistik untuk tujuan penilaian biodiversiti. Untuk kajian ini, kami membanding data daripada survei iDNA dan perangkap kamera dalam jangka masa yang sama. Kami mengumpul pacat secara berulang dari 64 stesen perangkap kamera di Sabah, Malaysia. Kami menggunakan model occupancy untuk menganalisis data iDNA dan perangkap kamera secara berasingan. Kemudian, kami mengabung data dari iDNA dan perangkap kamera dalam satu model. Kami mendapati bahawa anggaran occupancy dari data perangkap kamera dan iDNA adalah konsisten. Ini menunjukkan bahawa kaedah iDNA boleh digunakan untuk mengkaji dan memantau hidupan liar di hutan hujan tropika. Walau bagaimanapun, pengumpulan pacat perlu dibuat secara kerap lagi untuk memperolehi data yang seragam dengan perangkap kamera. Dengan adanya segelintir spesies yang hanya dikesan dengan iDNA, kaedah ini boleh digunakkan untuk melengkapi data dari perangkap kamera. Sinthesis dan aplikasi . Kajian ini merupakan satu cara untuk menganalisis data yang diperolehi dari pacat dengan menggunakan rangka kerja occupancy . Kami juga mengabungkan data iDNA dan perangkap kamera, yang meningkatkan ketepatan anggaran occupancy . Kaedah ini tidak terhad kepada pacat saja, tetapi boleh digunakan untuk analisis iDNA yang lain dan juga DNA yang diperolehi dari alam sekitar (eDNA). Kajian kami merupakan langkah pertama untuk mengalihkan focus kaedah iDNA dari kaedah survei ad‐hoc ke kaedah survey sistematik yang boleh digunakan untuk pemantauan hidupan liar dalam janka masa panjang.